More than spectators, visionaries (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
The paper aims to highlight theoretical reflections and project implications about technological interactivity within the artistic research of Studio Azzurro, setting them in a constellation of relations and affinities with the context of reference. The distinctiveness of the Milan-based collective, founded in 1982, has been shaped around the concept of “socializing interactivity.” This phenomenon stems from a design process that involves a constant negotiation between narratives, space, bodies and technologies, conceived as a system of relationships mediated by “natural interfaces.”The study traces the roots of this placement back to the counter-information experiences of the 1970s and the intersection with the experimental theatre of the 1980s, evolving through the language of cinema and video. At the same time, Studio Azzurro research remains constantly focused on the physical and sensitive properties of space, objects, bodies (both real and virtual), and the potentialities of montage – understood both as video editing and as spatial dramaturgy.The paper finally considers the socio-political implications of this form of art, bringing the attention on the creation of “spaces of relationships” that foster community and intersubjectivity.This investigation situates Studio Azzurro’s contributions within the broader context of technological interactivity and its potential to reshape human experience and communication.
Keywords: Socializing Interactivity; Space of Relationship; Point of Being; Intersubjectivity; Unthought